The ape man - Beaudine, William, 1892-1970; Sarecky, Barney A.; Lugosi, Bela, 1882-1956; Banner Productions; Cinetel Films ([Los Angeles, CA] : Banner Productions, 1943)
Dr. James Brewster (Bela Lugosi) and his colleague Dr. Randall (Henry Hall) are involved in a series of scientific experiments which have caused him to transform into an ape-man. In an attempt to obtain a cure Brewster believes that it will be necessary to inject himself with recently drawn human spinal fluid. When Randall refuses to help him by providing the fluid, Brewster and his captive gorilla must attempt to find an appropriate donor. --
Originally released as a motion picture in 1943.
Bela Lugosi, Louise Currie, Wallace Ford, Henry Hull, Minerva Urecal, Emil Van Horn.
Cinematographer, Mack Stengler; editor, Carl Pierson; musical director, Edward Kay.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed November 25, 2015).
Keywords: Scientists -- Drama; Monsters -- Drama; Self-experimentation in medicine -- Drama; Horror films; Mad scientist films; Fiction films; Feature films; Internet videos; Streaming video